Management of black scurf (Rhizoctonia solani) and common scab (Streptomyces scabies) of potato through eco-friendly components - S.M. CHAUDHARI, NARENDRA SINGH* and (Indian Phytopathology, 2012)
Black scurf (Rhizoctonia solani) and common scab (Streptomyces scabies) diseases of potato are becoming prominent in many potato growing districts of Gujarat state resulting in economic losses, since a decade. An experiment was conducted to find out more economical and eco-friendly management approaches, taking cv. Kufri Badshah with thirteen treatments involving bioagents (Trichoderma viride, T.harzianum and Bacillus subtilis strain B5), botanicals [Neem bann, onion (Allium cepa L.) bulb extract and garlic (Allium sativum L.) clove extract], organic amendment (farm yard manure) and boric acid applied individually or in combination. Seed tuber treatment (spray) with 2 per cent boric acid before storage followed by T. viride @ 8g/kg tuber treatment at planting registered the minimum black scurf incidence (6.42%) and index (0.17). Disease incidence was reduced by 81.22 % and severity index by 90.17 %. In case of common scab, tuber treatment with 3 per cent boric acid followed by B. subtilis tuber treatment @ 2.5g/kg recorded the lowest disease incidence (31.62%) and index (1.76). These treatments can provide an effective, economical and eco-friendly management of potato tuber diseases.